Preparation method of gel casting yttrium oxide ceramic

Through gel injection molding technology and powder pretreatment technology, combined with boric acid modified yttrium oxide and calcium carbonate doping, the problem of yttrium oxide ceramics prone to expansion and cracking at high temperatures is solved, and the preparation of high-performance yttrium oxide ceramics is realized, with high strength, toughness and wear resistance, and reduced processing margin and cost.

CN119822831AActive Publication Date: 2025-04-15XINYI XIYI ADVANCED MATERIALS RES INST OF IND TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411930778.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-15
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Yttrium oxide ceramics are prone to expand and crack at high temperatures, and their limitations in thermal shock resistance and high sintering temperatures hinder their widespread use.

Method used

Using gel injection molding technology, an aqueous suspension containing yttrium oxide and calcium oxide is prepared through powder pretreatment, combined with boric acid modified yttrium oxide and calcium carbonate doping to form high-performance yttrium oxide ceramics.

Benefits of technology

The high strength, toughness and wear resistance of yttrium oxide ceramics are achieved, which reduces processing allowance and cost, and improves thermal shock resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005210239560000011
    Figure HDA0005210239560000011
  • Figure HDA0005210239560000012
    Figure HDA0005210239560000012
Patent Text Reader

Abstract

The invention discloses a gel casting yttrium oxide ceramic preparation method, which comprises: preparing modified yttrium oxide powder, adding calcium carbonate, mixing, adopting an Isobam gelling agent to carry out green gel casting, and sintering to obtain the yttrium oxide ceramic. Through a powder pretreatment process, an aqueous suspension containing yttrium oxide and calcium oxide is obtained, and the dual problems of yttrium oxide sintering characteristic challenge and thermal shock susceptibility are solved. The preparation process is simple, the adopted gel system is non-toxic, harmless, environment-friendly and high in production efficiency, and the prepared ceramic has the advantages of high strength, good toughness, good wear resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic ceramic material preparation, in particular to a gel injection molding yttria ceramic and a preparation method thereof. Background Art

[0002] At present, ceramic materials have become an indispensable key in alloy smelting and casting, especially in titanium aluminum alloy smelting and casting. Due to the high chemical reactivity of molten titanium alloy, it can interact with almost all refractory materials. Commonly used oxide refractory materials have good thermodynamic stability in reaction with titanium aluminum alloy. Y2O3 and CaO are the most promising ceramic shell materials for titanium aluminum alloy casting.

[0003] Studies have shown that the reaction between calcium oxide and titanium liquid is relatively weak, however, there are challenges in the practical application of yttrium oxide as a shell material. The yttrium oxide shell has a certain degree of hygroscopicity, which easily leads to volume expansion and cracking after contact with high temperatures. Therefore, strict humidity requirements must be met, which increases the complexity of the practical application of yttrium oxide as a shell material. Although yttrium oxide is recognized as the most stable oxide refractory material, its limitations in thermal shock resistance and high sintering temperature have hindered its widespread adoption.

[0004] Traditional methods for preparing yttrium oxide composite ceramics include injection molding and slip casting, but it is difficult to prepare high-performance yttrium oxide ceramics. At present, green gel injection molding is mostly used, which forms a macromolecular network structure or a ceramic network structure through chemical reactions inside the slurry, so that the ceramic slurry poured into the non-porous mold can quickly solidify into a ceramic body. The structure and density of the molded product are uniform, the gel injection molding cycle is short, the performance is reliable, and it is conducive to industrial application production. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing yttrium oxide ceramics by gel injection molding. The present invention adopts a gel casting method to prepare oxide refractory materials. This molding method realizes the multifunctional production of yttrium oxide refractory products of various complex shapes. Through a powder pretreatment process, an aqueous suspension containing yttrium oxide and calcium oxide is successfully obtained, which also solves the dual problems of yttrium oxide sintering characteristic challenges and thermal shock susceptibility. The preparation process of the present invention is simple, the gel system used is non-toxic and harmless, environmentally friendly, and has high production efficiency. The prepared ceramics can have the advantages of high strength, good toughness, good wear resistance, etc.

[0006] The technical solution adopted by the present invention is as follows: A method for preparing yttria ceramics by gel injection molding, comprising the following steps:

[0007] Step 1: First, yttrium oxide powder is ultrasonically dispersed in a boric acid solution at 45-60° C., and then dried and sieved to obtain modified yttrium oxide powder;

[0008] Step 2: adding deionized water, modified yttrium oxide powder and calcium carbonate into a ball mill, mixing and dispersing, drying, sieving and calcining to obtain calcium oxide-doped modified yttrium oxide powder;

[0009] Step 3: Mix the Isobam gelling agent with ultrapure water, and then adjust the pH value to 8-10 with lactic acid and tetramethylammonium hydroxide to obtain a premixed solution, and finally add calcium oxide-doped modified yttrium oxide powder and a sintering aid to the premixed solution, and obtain a slurry by ball milling;

[0010] Step 4: inject the slurry into a mold after vacuum degassing, solidify and shape it under microwave heating conditions, and dry it after demolding to obtain a yttrium oxide ceramic body; finally, sinter the ceramic body in a vacuum sintering furnace, and anneal it in a muffle furnace after sintering to obtain a yttrium oxide ceramic.

[0011] Preferably, in step one, the yttrium oxide powder has three different particle sizes (d50 is 50 μm, 3 μm, and 550 nm, respectively), and the ratio of the addition amount of different particle sizes is 5:3:2; the amount of yttrium oxide added is 40-60 wt%; the heating and ultrasonic time is 0.5-1 h; the mass concentration of the boric acid solution is 5-10%; the drying temperature is 80-100 ° C, the drying time is 18-24 h, and passed through a 120 mesh sieve.

[0012] Preferably, in step 2, the modified yttrium oxide powder accounts for 40-60% of the mass of the mixed solution, and the mass of calcium carbonate accounts for 5%-10% of the modified yttrium oxide powder; the drying temperature is 80-100°C, the drying time is 18-24h, and the mixture is sieved through a 120-mesh sieve; the calcination temperature is 800-850°C, and the calcination time is 8-10h.

[0013] Preferably, in step three, the Isobam gelling agent is one or more of Isobam104, Isobam110, and Isobam304, which are fully dissolved in ultrapure water to prepare a solution with a concentration of 10-20wt%, and the pH value is adjusted to 8-10 by lactic acid and tetramethylammonium hydroxide.

[0014] Preferably, in step three, the mass solid content of the calcium oxide doped modified yttrium oxide powder in the slurry is 60-75%; the sintering aid is zirconium oxide, and the added amount is 0.5-1wt% of the calcium oxide doped modified yttrium oxide powder.

[0015] Preferably, in step 4, the vacuum degassing pressure is -0.5 to -1 MPa, and the vacuum degassing time is 40-60 min; the microwave heating temperature is 30-40°C, and the curing time is 5-10 min; the specific drying process is: drying in a constant temperature and humidity chamber with a humidity of 70-85% and a temperature of 35-50°C for 15-20 h.

[0016] Preferably, in step 4, the specific sintering process is: heating to 800°C at a rate of 1-5°C / min, keeping warm for 1-2h, heating to 1650-1720°C at a rate of 1-3°C / min, and keeping warm for 2-4h.

[0017] Preferably, in step 4, the sintered ceramic is placed in a muffle furnace and annealed in air at 1000-1100° C. for 2-3 hours.

[0018] Preferably, in step 2 and step 3, the grinding balls used in ball milling are zirconia balls, the ball-to-material ratio is 1:1-3, the ball milling speed is 300-500 r / min, and the ball milling time is 12-24 h.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention uses boric acid to modify yttrium oxide to prevent its hydrolysis, and this process also adapts the Zeta potential value to that of calcium carbonate, thereby increasing the powder stability and reducing the slurry viscosity.

[0021] (2) The present invention adds calcium carbonate, which is dried, sieved, and calcined to obtain calcium oxide-doped modified yttrium oxide powder, which is beneficial to the densification of yttrium oxide, accelerates the diffusion of yttrium oxide grain boundaries, and improves the flexural strength of yttrium oxide.

[0022] (3) The green gelcasting technology adopted by the present invention has a simple process, can obtain a slurry with good dispersibility, can form yttria ceramics with complex shapes, and has high strength of the ceramic body. The most important thing is that the drying shrinkage and sintering shrinkage of the samples prepared by this gel system are uniform and calculable, the processing allowance is small, and the subsequent processing is greatly reduced, which is lower in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the SEM spectrum of the yttria ceramic prepared in Example 1.

[0024] Figure 2 This is a physical picture of the yttrium oxide ceramic prepared in Example 1. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0026] Example 1

[0027] Step 1: First, 100g of yttrium oxide powder (d 5050 g, 30 g, and 20 g of 50 μm, 3 μm, and 550 nm powders were added respectively) and ultrasonically dispersed in 250 g of a 5% boric acid solution under heating conditions at 45° C., heated and ultrasonicated for 0.5 h, dried at 80° C. for 18 h, and passed through a 120-mesh sieve to obtain a modified yttrium oxide powder;

[0028] Step 2: Add 250g of deionized water, 100g of modified yttrium oxide powder, and 5g of calcium carbonate into a ball mill and mix and disperse. The grinding balls used in the ball mill are zirconium oxide balls, the ball-to-material ratio is 1:1, the ball mill speed is 500r / min, and the ball milling time is 24h. Dry at 80℃ for 24h, pass through a 120-mesh sieve, and calcine at 800℃ for 10h to obtain calcium oxide-doped modified yttrium oxide powder;

[0029] Step 3: Add 10g of Isobam104 gelling agent to 100g of deionized water to prepare a solution with a concentration of 10wt%, and then adjust the pH value to 8 with lactic acid and tetramethylammonium hydroxide to obtain a premixed solution, and finally add 60g of calcium oxide-doped modified yttrium oxide powder and 0.3g of zirconium oxide to the premixed solution; add 180g of zirconium oxide balls, ball mill speed is 500r / min, ball mill for 24h to mix and obtain calcium oxide-doped modified yttrium oxide slurry;

[0030] Step 4: The calcium oxide doped modified yttrium oxide slurry is injected into the mold after vacuum degassing, the vacuum degassing pressure is -0.5MPa, and the vacuum degassing time is 60min; it is cured for 5min under the condition of microwave heating temperature of 30°C to form; after demolding, it is dried in a constant temperature and humidity chamber with a humidity of 70% and a temperature of 35°C for 15h to obtain a calcium oxide doped modified yttrium oxide green body; finally, the ceramic green body is sintered in a sintering furnace, and the specific sintering process is: heating to 800°C at a rate of 1°C / min, keeping warm for 1h, heating to 1650°C at a rate of 1°C / min, keeping warm for 2h, and then annealing the obtained ceramic in air at 1000°C in a muffle furnace for 3 hours to obtain calcium oxide doped modified yttrium oxide ceramics.

[0031] The SEM image of the ceramic is shown in Figure 1 As shown, the ceramic grains are uniform, without obvious pores, and show a higher density; ceramic fractures are mostly transgranular fractures, which reflects that the energy consumed when the ceramic breaks is large and the ceramic has a higher strength.

[0032] The actual picture of the ceramic is as follows Figure 2 As shown, it can be seen that the prepared ceramic has a diameter of 80 mm and a smooth surface without defects.

[0033] Example 2

[0034] Step 1: First, 125g of yttrium oxide powder (d 5075 g, 30 g, and 20 g of 50 μm, 3 μm, and 550 nm powders were added respectively) and ultrasonically dispersed in 250 g of a 7.5% boric acid solution under heating conditions at 50° C., heated and ultrasonicated for 45 min, dried at 90° C. for 20 h, and passed through a 120-mesh sieve to obtain a modified yttrium oxide powder;

[0035] Step 2: Add 250g of deionized water, 125g of modified yttrium oxide powder, and 9.375g of calcium carbonate into a ball mill and mix and disperse. The grinding balls used in the ball mill are zirconium oxide balls, the ball-to-material ratio is 1:2, the ball mill speed is 400r / min, and the ball milling time is 18h. Dry at 85℃ for 22h, pass through a 120-mesh sieve, and calcine at 850℃ for 9h to obtain calcium oxide-doped modified yttrium oxide powder;

[0036] Step 3: Add 15g of Isobam104 gelling agent to 100g of deionized water to prepare a solution with a concentration of 15wt%, and then adjust the pH value to 9 with lactic acid and tetramethylammonium hydroxide to obtain a premixed solution, and finally add 70g of calcium oxide-doped modified yttrium oxide powder and 0.456 zirconium oxide to the premixed solution; add 166g of zirconium oxide balls, ball mill speed is 400r / min, ball mill for 20h to mix and obtain calcium oxide-doped modified yttrium oxide slurry;

[0037] Step 4: The calcium oxide doped modified yttrium zirconium oxide slurry is injected into the mold after vacuum degassing, the vacuum degassing pressure is -0.7MPa, and the vacuum degassing time is 50min; it is cured for 7min under the condition of microwave heating temperature of 35°C to form; after demolding, it is dried in a constant temperature and humidity chamber with humidity of 75% and temperature of 40°C for 18h to obtain a calcium oxide doped modified yttrium oxide ceramic body; finally, the ceramic body is sintered in a sintering furnace, and the specific sintering process is: heating to 800°C at a rate of 3°C / min, keeping warm for 1h, heating to 1680°C at a rate of 2°C / min, keeping warm for 4h, and then annealing the obtained ceramic in air at 1050°C in a muffle furnace for 2.5 hours to obtain a calcium oxide doped modified yttrium oxide ceramic.

[0038] Example 3

[0039] Step 1: First, 150g of yttrium oxide powder (d 50 50 g, 50 g, and 50 g of 50 μm, 3 μm, and 550 nm powders were added respectively) and ultrasonically dispersed in 250 g of 9% boric acid solution under heating conditions at 55° C., heated and ultrasonicated for 1 h, dried at 90° C. for 20 h, and passed through a 120-mesh sieve to obtain modified yttrium oxide powder;

[0040] Step 2: Add 250g of deionized water, 150g of modified yttrium oxide powder, and 10.5g of calcium carbonate into a ball mill and mix and disperse. The grinding balls used in the ball mill are zirconium oxide balls, the ball-to-material ratio is 1:2, the ball mill speed is 350r / min, and the ball milling time is 20h. Dry at 90℃ for 22h, pass through a 120-mesh sieve, and calcine at 875℃ for 8.5h to obtain calcium oxide-doped modified yttrium oxide powder;

[0041] Step 3: Add 20g of Isobam104 gelling agent to 100g of deionized water to prepare a solution with a concentration of 20wt%, and then adjust the pH value to 10 with lactic acid and tetramethylammonium hydroxide to obtain a premixed solution, and finally add 75g of calcium oxide-doped modified yttrium oxide powder and 0.75g of zirconium oxide to the premixed solution; add 510g of zirconium oxide balls, ball mill speed is 300r / min, ball mill for 18h to mix and obtain calcium oxide-doped modified yttrium oxide slurry;

[0042] Step 4: The calcium oxide doped modified yttrium oxide slurry is injected into the mold after vacuum degassing, the vacuum degassing pressure is -1MPa, and the vacuum degassing time is 60min; it is cured for 10min under the condition of microwave heating temperature of 40°C to form; after demolding, it is dried in a constant temperature and humidity chamber with humidity of 85% and temperature of 50°C for 15h to obtain a calcium oxide doped modified yttrium oxide ceramic body; finally, the ceramic body is sintered in a sintering furnace, and the specific sintering process is: heating to 800°C at a rate of 5°C / min, keeping warm for 2h, heating to 1700°C at a rate of 3°C / min, keeping warm for 5h, and then annealing the obtained ceramic in air at 1000°C in a muffle furnace for 2 hours to obtain a calcium oxide doped modified yttrium oxide ceramic.

[0043] Example 4

[0044] Step 1: First, 137.5 g of yttrium oxide powder (d 50 77.5 g, 30 g, and 30 g of 50 μm, 3 μm, and 550 nm powders were added respectively) and ultrasonically dispersed in 250 g of 10% boric acid solution under heating conditions at 60° C., heated and ultrasonicated for 50 min, dried at 100° C. for 18 h, and passed through a 120-mesh sieve to obtain modified yttrium oxide powder;

[0045] Step 2: Add 250g of deionized water, 137.5g of modified yttrium oxide powder, and 11g of calcium carbonate into a ball mill and mix and disperse. The grinding balls used in the ball mill are zirconium oxide balls, the ball-to-material ratio is 1:3, the ball mill speed is 300r / min, and the ball milling time is 24h. Dry at 100℃ for 18h, pass through a 120-mesh sieve, and calcine at 900℃ for 8h to obtain calcium oxide-doped modified yttrium oxide powder;

[0046] Step 3: 20g of Isobam104 gelling agent is mixed with deionized water to obtain a solution with a concentration of 20wt%, and then the pH value is adjusted to 8 by lactic acid and tetramethylammonium hydroxide to obtain a premixed solution, and finally 70g of calcium oxide doped modified yttrium oxide and 0.63g of zirconium oxide are added to the premixed solution; 340g of zirconium oxide balls are added, the ball milling speed is 450r / min, and the ball milling is performed for 24h to obtain a calcium oxide doped modified yttrium oxide slurry;

[0047] Step 4: The calcium oxide doped modified yttrium oxide slurry is injected into the mold after vacuum degassing, the vacuum degassing pressure is -1MPa, and the vacuum degassing time is 60min; it is cured for 6min under the condition of microwave heating temperature of 30°C; after demolding, it is dried in a constant temperature and humidity chamber with humidity of 80% and temperature of 40°C for 18h to obtain a calcium oxide doped modified yttrium oxide ceramic body; finally, the ceramic body is sintered in a sintering furnace, and the specific sintering process is: heating to 800°C at a rate of 2°C / min, keeping warm for 2h, heating to 1720°C at a rate of 3°C / min, keeping warm for 3.5h, and then annealing the obtained ceramic in air at 1100°C in a muffle furnace for 2 hours to obtain a calcium oxide doped modified yttrium oxide ceramic.

[0048] Comparative Example

[0049] Step 1: First, 120g of yttrium oxide powder (d 50 70 g, 30 g, and 20 g of 50 μm, 3 μm, and 550 nm powders were added respectively) and ultrasonically dispersed in 250 g of a 10% boric acid solution at 60° C., heated and ultrasonicated for 50 min, dried at 100° C. for 18 h, and passed through a 120-mesh sieve to obtain modified yttrium oxide powder;

[0050] Step 2: Add 250g of deionized water and 137.5g of modified yttrium oxide powder into a ball mill and mix and disperse. The grinding balls used in the ball mill are zirconium oxide balls, the ball-to-material ratio is 1:3, the ball mill speed is 300r / min, and the ball milling time is 24h. Dry at 100℃ for 18h, pass through a 120-mesh sieve, and calcine at 900℃ for 8h to obtain modified yttrium oxide powder;

[0051] Step 3: 20g of Isobam104 gelling agent is mixed with deionized water to prepare a solution with a concentration of 20wt%, and then the pH value is adjusted to 8 by lactic acid and tetramethylammonium hydroxide to obtain a premixed solution, and finally 70g of modified yttrium oxide and 0.63g of zirconium oxide are added to the premixed solution; 340g of zirconium oxide balls are added, the ball milling speed is 450r / min, and the ball milling is performed for 24h to obtain a modified yttrium oxide slurry;

[0052] Step 4: The modified yttrium oxide slurry is injected into the mold after vacuum degassing, the vacuum degassing pressure is -1MPa, and the vacuum degassing time is 60min; it is cured for 6min under the condition of microwave heating temperature of 30℃; after demolding, it is dried in a constant temperature and humidity chamber with humidity of 80% and temperature of 40℃ for 18h to obtain a modified yttrium oxide ceramic body; finally, the ceramic body is sintered in a sintering furnace, and the specific sintering process is: heating to 866℃ at a rate of 2℃5min, keeping warm for 2h, heating to 1726℃ at a rate of 3℃5min, keeping warm for 3.5h, and then annealing the obtained ceramic in air at 1666℃ in a muffle furnace for 2 hours to obtain a modified yttrium oxide ceramic.

[0053] The properties of the ceramics obtained in Examples 1-4 and Comparative Examples are detailed in Table 1.

[0054] Table 1 Test results of ceramic properties obtained in Examples 1-4 and Comparative Examples

[0055] Example Strength (MPa) Thermal shock resistance (25℃-1166℃ thermal shock times) Example 1 76 25 Example 2 74 26 Example 3 81 28 Example 4 76 25 Comparative Example 55 12

[0056] Strength test: tested with a universal electronic testing machine. The test complies with GB5T 3661-2617.

[0057] Thermal shock resistance test: The test was conducted using a ceramic thermal stability tester in accordance with GB5T36873-2614. The comparative example was yttrium oxide ceramics that had not been modified by calcium oxide doping.

[0058] As shown in Table 1, the strength of the calcium oxide-doped modified yttrium oxide ceramics prepared by the present invention exceeds 76 MPa, and there is no crack after more than 25 thermal shocks at 25°C-1166°C, indicating that it has excellent mechanical properties and higher thermal shock resistance.

[0059] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a gel-casting yttria ceramic, characterized in that: The following steps are involved: Step 1: firstly, dispersing yttrium oxide powder in a boric acid solution under ultrasonic conditions at 45-60°C, and obtaining modified yttrium oxide powder by drying and sieving; Step 2: adding deionized water, modified yttrium oxide powder and calcium carbonate into a ball mill, mixing and dispersing, and obtaining calcium oxide-doped modified yttrium oxide powder after drying, sieving and calcining; Step 3: Mix the Isobam gelling agent with ultrapure water, and then adjust the pH value to 8-10 with lactic acid and tetramethylammonium hydroxide to obtain a premixed solution, and finally add calcium oxide-doped modified yttrium oxide powder and a sintering aid to the premixed solution, and obtain a slurry by ball milling; Step 4: inject the slurry into a mold after vacuum degassing, solidify and shape it under microwave heating conditions, and dry it after demolding to obtain a yttrium oxide ceramic body; finally, sinter the ceramic body in a vacuum sintering furnace, and anneal it in a muffle furnace after sintering to obtain a yttrium oxide ceramic.

2. The method for preparing a gel-casting yttria ceramic according to claim 1, characterized in that: In step 1, the yttrium oxide powder has three different particle sizes, d 50 The sizes of the particles are 50 μm, 3 μm and 550 nm respectively, and the ratio of the added amount of different particle sizes is 5:3:2; the added amount of yttrium oxide is 40-60 wt%; the heating and ultrasonic time is 0.5-1 h; the mass concentration of the boric acid solution is 5-10%; the drying temperature is 80-100 ° C, the drying time is 18-24 h, and the particles are sieved through a 120 mesh sieve.

3. The method for preparing a gel-casting yttria ceramic according to claim 1, characterized in that: In step 2, the modified yttrium oxide powder accounts for 40%-60% of the mass of the mixed solution, and the mass of calcium carbonate accounts for 5%-10% of the modified yttrium oxide powder; the drying temperature is 80-100°C, the drying time is 18-24h, and the mixture is sieved through a 120-mesh sieve; the calcination temperature is 800-850°C, and the calcination time is 8-10h.

4. The method for preparing a gel-casting yttria ceramic according to claim 1, characterized in that: In step 3, the Isobam gelling agent is one or more of Isobam104, Isobam110, and Isobam304, which are fully dissolved in ultrapure water to prepare a solution with a concentration of 10-20wt%.

5. The method for preparing a gel-casting yttria ceramic according to claim 1, characterized in that: In step three, the mass solid content of the calcium oxide-doped modified yttrium oxide powder in the slurry is 60-75%; the sintering aid is zirconium oxide, and the added amount is 0.5-1wt% of the calcium oxide-doped modified yttrium oxide powder.

6. The method for preparing a gel-casting yttria ceramic according to claim 1, characterized in that: In step 4, the vacuum degassing pressure is -0.5 to -1 MPa, and the vacuum degassing time is 40-60 minutes; the microwave heating temperature is 30-40°C, and the curing time is 5-10 minutes; the specific drying process is: drying in a constant temperature and humidity box with a humidity of 70-85% and a temperature of 35-50°C for 15-20 hours.

7. The method for preparing a gel-casting yttria ceramic according to claim 1, characterized in that: In step 4, the specific sintering process is: heating to 800°C at a rate of 1-5°C / min, keeping warm for 1-2h, heating to 1650-1720°C at a rate of 1-3°C / min, and keeping warm for 2-4h.

8. The method for preparing a gel-casting yttria ceramic according to claim 1, characterized in that: In step 4, the sintered ceramic is placed in a muffle furnace and annealed in air at 1000-1100° C. for 2-3 hours.

9. The method for preparing a gel-casting yttria ceramic according to claim 1, characterized in that: In step 2 and step 3, the grinding balls used in ball milling are zirconia balls, the ball-to-material ratio is 1:1-3, the ball milling speed is 300-500r / min, and the ball milling time is 12-24h.

Citation Information

Patent Citations

  • Ceramic shell molds and cores for casting of reactive metals

    CA1339184C

  • Method for preparing compact yttria ceramics

    CN101628812A

  • Preparation method of rare-earth-doped yttrium oxide laser ceramic optical fiber

    CN105565810A

  • Method for preparing yttrium oxide refractory material product through gel casting and crucible

    CN114380596A

  • Production of transparent yttrium oxide sintered body

    JP1998273364A